2019
DOI: 10.1016/j.redox.2019.101173
|View full text |Cite
|
Sign up to set email alerts
|

2-O-β-d-glucopyranosyl- -ascorbic acid, a novel vitamin C derivative from Lycium barbarum, prevents oxidative stress

Abstract: Reducing agents are crucial for the management of maladaptive inflammation-induced macrophage death and hematopoietic toxicity of chemotherapy. 2-O-β-d-glucopyranosyl-l-ascorbic acid (AA-2βG), a unique AA (or vitamin C) derivative identified in Lycium barbarum, exhibited enhanced free radical scavenging activity compared with AA and its synthetic derivative AA-2αG. AA-2βG protected hydrogen peroxide-induced cell death in murine macrophage RAW264.7 cells. Treatment with AA-2βG eliminated oxidative stress and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to the previous study, AA-2βG could exhibit the activities of AA to some extent . It has been proved that AA-2βG has strong antioxidant activity in vitro and in vivo and can reduce the extent of inflammation in dextran sodium sulfate-induced colitis by regulating gut microbiota . It has been reported that the polysaccharides from the fruits and bee-collected pollen of L.…”
Section: Introductionmentioning
confidence: 95%
“…According to the previous study, AA-2βG could exhibit the activities of AA to some extent . It has been proved that AA-2βG has strong antioxidant activity in vitro and in vivo and can reduce the extent of inflammation in dextran sodium sulfate-induced colitis by regulating gut microbiota . It has been reported that the polysaccharides from the fruits and bee-collected pollen of L.…”
Section: Introductionmentioning
confidence: 95%
“…AA-2βG protected hydrogen peroxide-induced cell death in murine macrophage RAW264.7 cells. Treatment with AA-2βG eliminated oxidative stress and the ratio of cellular glutathione to glutathione disulfide more effectively than AA and AA-2αG [128]. Reported three times higher anti oxidant properties of than rutin, measured by the action radical scavenging activity by the Ferric-Reducing Activity of Plasma (FRAP) test.…”
Section: Ascorbic Acid (Aa)mentioning
confidence: 97%
“…Intracellular ROS, Hydrogen Peroxide (H 2 O 2 ), and Superoxide Measurements. Intracellular ROS levels were measured in the lungs or macrophages using 2 ′ ,7 ′ -dichlorofluorescin diacetate (DCFH-DA; Sigma, USA), which is oxidized to form fluorescent DCF products by excessive free radicals [38][39][40][41][42]. Briefly, the lung homogenates or cells were incubated with DCFH-DA (20 μmol/L) for 1 h at 37°C in the dark, and then DCF fluorescence intensity was detected by a multidetection reader at an excitation/emission wavelength of 485/535 nm.…”
Section: Detection Of Lactate Dehydrogenase (Ldh) Nuclearmentioning
confidence: 99%